2023
DOI: 10.1097/jtn.0000000000000692
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Thoracic CT Decision Rule in the Evaluation of Injured Children: A Quality Improvement Initiative

Abstract: Background: Differences in injury patterns in children suggest that life-threatening chest injuries are rare. Radiation exposure from computed tomography increases cancer risk in children. Two large retrospective pediatric studies have demonstrated that thoracic computed tomography can be reserved for patients based on mechanism of injury and abnormal findings on chest radiography. Objective: Implement a decision rule to guide utilization of thoracic computed tomography in the evaluation of pediatric blunt t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…These post‐guidance publication peaks and subsequent fall in use of the recommended protocol suggest that clinicians need reminding of the recommendations, with further information dissemination and education required both at a national and local level. A recent study showed that the use of a thoracic imaging decision tool reduced the use of CT in pediatric acute trauma by 50% 17 without an increase in missed, clinically significant, injuries.…”
Section: Discussionmentioning
confidence: 99%
“…These post‐guidance publication peaks and subsequent fall in use of the recommended protocol suggest that clinicians need reminding of the recommendations, with further information dissemination and education required both at a national and local level. A recent study showed that the use of a thoracic imaging decision tool reduced the use of CT in pediatric acute trauma by 50% 17 without an increase in missed, clinically significant, injuries.…”
Section: Discussionmentioning
confidence: 99%